Study on flexural behavior of spliced shallow composite beams with different shear connectors. (15th February 2022) - Gao, Shan; Bai, Qi; Guo, Lanhui; Kang, Shao-Bo; Derlatka, Anna; Deng, Senwen
Highlights: Two spliced shallow composite beams with different shear connectors were tested. Compared with slotted web shear connectors, the beam relying on steel–concrete bond force show better flexural behavior. The prediction formula for the flexural capacity of the beams is deduced and validated. Bond-slip behavior between beam and slab is developed by using spring element. Shallow composite beams with partially shear connection show excellent ability of stress redistribution. Abstract: The flexural behavior of spliced shallow composite beams with different shear connectors including steel–concrete bond force and slotted webs were experimentally studied in detail. Finite element models by using spring element to consider the bond-slip behavior between steel beam and concrete slab are developed and validated against the test results. The prediction formula for the flexural capacity of the beams is deduced and validated. The analysis results show that compared with the beam using slotted web shear connectors, the beam relying on steel–concrete bond force shows better flexural capacity and ductility. Both the beams failed in ductile failure mode. The shallow composite beams with partial shear connection have the excellent ability of stress redistribution which would be improved by decreasing the shear transfer coefficient. Through the comparison with the experimental results and numerical results, the prediction formula proposed in this paper for the flexural capacity of the composite beam with partial shear connection shows better accuracy than Eurocode.